Temperature-related growth limits and wood decay capacity of the warmth-loving fungus Biscogniauxia nummularia in vitro - Tropf, Jan; Bien, Steffen; Bußkamp, Johanna; Sennhenn-Reulen, Holger; Becker, Johanna; Grüner, Jörg; Langer, Gitta Jutta; Langer, Ewald Johannes (Frontiers in Fungal Biology, 2025)
Temperature-related growth characteristics and wood decay capacities of Biscogniauxia nummularia strains were analysed in vitro, revealing variability between strains. To model the growth characteristics fitted dose-response curves were generated using the four-parameter Brain-Cousens hormesis model. The different strains showed distinct optimum growth temperatures, with some achieving maximum growth at 25°C, while others peaked at 28°C, depending on the tested culture media. Strains tested also exhibited variation in their temperature ranges for measurable growth, with some tolerating a broader range than others. The results of the study lead to the consideration that temperature tolerance as well as the optimal growth temperature might be influenced by the strains’ geographic origin, with those from southern Germany possibly adapted to higher temperatures. In terms of wood decay, mass loss caused by the various strains differed clearly in many cases, suggesting potential strain-dependent differences in pathogenicity. Additionally, genetic analysis of the beta-tubulin DNA region of B. nummularia specimens examined revealed considerable variations between the strains.